THE ROLE OF E-COMMERCE PLATFORMS IN DRIVING THE ECONOMIC GROWTH OF MSMEs IN INDONESIA - Apriliyah Hidayat (CURVE: Journal of Economic, Business and Accounting, 2025)
Indonesia's MSMEs are projected to reach 65.5 million units by 2025, contributing 61.9% of GDP and 97% of the workforce. However, they face challenges in market access, capital, and digital literacy, which are addressed through e-commerce platforms like Shopee and Tokopedia via the MSME Go Digital program. This study aims to describe the role of e-commerce platforms in expanding MSME market access and analyze their contribution to increased productivity and income. Using a qualitative descriptive approach with secondary data from government reports, journals (JRIME, JDEP), and surveys (Ipsos), content analysis and source triangulation were applied to classify the findings into e-commerce developments, platform roles, economic impacts, and challenges. The results indicate an e-commerce transaction value of IDR 471 trillion (26% growth), a 25-40% increase in MSME turnover via live shopping and analytics features, a 20-30% reduction in operational costs, and a higher GDP contribution, despite constraints on digital literacy (70% of MSMEs in rural areas) and infrastructure.